Characterization of patients operated on for gastric adenocarcinoma at "Dr. Carlos J. Finlay" Hospital from 2009 to 2016 - Yoan Gabriel Rodríguez Martínez; Ibrain Rodriguez Rodriguez; René Borges Sandrino; Enia Remón Musibay (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Gastric cancer is the fourth most common cancer at present and the second leading cause of cancer-related mortality worldwide. Objective: The aim of this study is to characterize the patients with gastric adenocarcinoma operated on at "Dr. Carlos J. Finlay" Hospital during the period between 2009 and 2016. Material and Methods: A descriptive retrospective study was conducted in patients operated on for gastric adenocarcinoma in an eight-year period. Results: Male geriatric patients prevailed in the study. Gastric ulcer was the most frequent form of presentation in 54,7 %. Tumors of the antrum predominated in 72,0 %, with moderate degree of differentiation in 61,3 % of patients. The majority of tumors were in stage IIIA. The most used surgical methods were distal gastrectomy which was performed in 56,0 % of patients and exeretic procedures that were carried out in 68,0 % of patients. Operative mortality was 6,0 % with prevalence of hypovolemic shock. Conclusion: There was a predominance of male geriatric patients who underwent the surgical technique of distal gastrectomy. Gastric ulceration was the most common clinical form of presentation as well as tumors of the antrum in stage IIIA, in which there was a moderate degree of differentiation. Advanced stage tumors and palliative procedures were significantly related to mortality.